Efficacy of an oil‐based formulation combining Metarhizium rileyi and nucleopolyhedroviruses against lepidopteran pests of soybean. (18th June 2020) - Lopes, Rogerio Biaggioni; Sosa‐Gómez, Daniel Ricardo; Oliveira, Charles Martins; Sanches, Marcio Martinello; de Souza, Daniela Aguiar; Benito, Norton Polo; Schmidt, Francisco Guilherme Vergolino; Faria, Marcos
Abstract: A biopesticide that combines Metarhizium rileyi and nucleopolyhedrovirus (NPV) in an oil dispersion (OD) was developed. Its efficacy against Anticarsia gemmatalis and Chrysodeixis includens was evaluated under laboratory and field conditions. First, each of the two selected fungal strains, combined or not in OD preparations with AgMNPV or ChinNPV, was tested in the laboratory against A. gemmatalis and C. includens, respectively. AgMNPV–fungus combinations had similar effect on overall mortality of A. gemmatalis compared to each pathogen used alone. C. includens was less susceptible to infection by M. rileyi strains, and ChinNPV became the major cause of larval death. The OD formulations with M. rileyi and/or NPV were applied in infested soybean fields. ChinNPV + M. rileyi caused 50.8% of overall mortality six days after spraying in a soybean crop infested by both pests, whereas for treatments with the fungus or the virus alone the percentages were 41.2% and 8.8%, respectively. In another field infested solely by A. gemmatalis, insect mortality was similar for the AgMNPV–fungus combination and the virus used alone. Larval parasitism by wasps and dipterans was not affected following biopesticide spraying. Our results suggest that the performance of a dual‐action biopesticide is related to the NPV and fungal strains that are combined and the proportion of host populations simultaneously infesting the crop.